2022
DOI: 10.1002/lio2.730
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal thoughts in patients with empty nose syndrome

Abstract: Objectives: Patients with empty nose syndrome (ENS) suffer from paradoxical nasal obstruction with a patent objective nasal airway. ENS may result from the excessive surgical reduction of the turbinate tissue. ENS patients also experience significant psychological symptoms such as anxiety and depression. In this study, we aimed to evaluate the prevalence of suicidal thoughts in ENS patients and to characterize these patients for early identification. Study Design: Prospective case series. Methods: Patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Another study also reported on a cohort of ENS individuals carrying a significant psychological burden and marked difficulties with many activities of daily life, suggesting a multimodal approach that included the surgical construction of tissues and cognitive–behavioral therapy (CBT) to address the psychological issue [ 13 ]. Our previous study also demonstrated that suicidal thoughts were frequently identified in patients with ENS [ 19 ]. Empty nose syndrome patients with suicidal thoughts experienced significantly more severe symptoms, impaired quality of life, and greater psychological burden than those without suicidal thoughts.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another study also reported on a cohort of ENS individuals carrying a significant psychological burden and marked difficulties with many activities of daily life, suggesting a multimodal approach that included the surgical construction of tissues and cognitive–behavioral therapy (CBT) to address the psychological issue [ 13 ]. Our previous study also demonstrated that suicidal thoughts were frequently identified in patients with ENS [ 19 ]. Empty nose syndrome patients with suicidal thoughts experienced significantly more severe symptoms, impaired quality of life, and greater psychological burden than those without suicidal thoughts.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the severity of preoperative psychological symptoms is an important determining factor for surgical outcomes and residual disease after nasal reconstruction surgery [ 18 ]. Suicidal ideation can be identified in up to 37.1% and 6.5% of patients with ENS before and after nasal reconstruction surgery, respectively [ 19 ]. Thus, it is important to evaluate psychological symptoms in patients with ENS, even after nasal reconstruction surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a common psychiatric health issue affecting an estimated 5% of adults worldwide. 39 However, approximately 70% of patients with ENS have been shown to experience depression 4 , 6 , 11 which is much higher than the global prevalence. In this present investigation, 68.6% presented a depressive status before surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review with six studies found that anxiety and depression were elevated in ENS patients (65%-73% and 51%-71%, respectively) [8] . One cross-sectional study found a high prevalence of anxiety and depression warranting treatment, with decreased productivity at work and other activities [14] . Symptom severity correlated with depression and anxiety severity, overall pain/ discomfort, and impairment in activities of daily living.…”
Section: Symptomsmentioning
confidence: 99%